2020
DOI: 10.1111/nmo.13913
|View full text |Cite
|
Sign up to set email alerts
|

Postmenopausal women with irritable bowel syndrome (IBS) have more severe symptoms than premenopausal women with IBS

Abstract: Background Although irritable bowel syndrome (IBS) is more common in women, little is known about the role of hormonal changes and menopause in IBS. This study aimed to evaluate for differences in gastrointestinal (GI) and psychological symptoms between pre‐ and postmenopausal women with IBS compared to age‐matched men with IBS. Methods Patients with Rome‐positive IBS were identified. Premenopausal women were <45 years of age with regular menses. Postmenopausal women were ≥45 years without menses for at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 65 publications
2
19
0
Order By: Relevance
“…Researchers have linked sex hormones with gastrointestinal functions given compelling evidence showing a higher prevalence of IBS or functional dyspepsia symptoms and/or a greater symptom severity in women compared to men [ 18 22 ]. Although the underlying mechanisms linking sex hormones and gastrointestinal disturbances remain to be elucidated, intestinal dysmotility, visceral hypersensitivity, intestinal barrier dysfunction and mucosal immune activation through a brain-gut axis are thought to be involved [ 4 , 12 , 18 , 21 , 22 ]. For example, higher mucosal immune activation was found in women with IBS compared with men with IBS, and mast cell infiltration was related to greater abdominal bloating and dysmotility-like dyspepsia symptoms in women with IBS [ 23 ].…”
Section: Factors Influencing Gastrointestinal Health In Midlife Womenmentioning
confidence: 99%
See 3 more Smart Citations
“…Researchers have linked sex hormones with gastrointestinal functions given compelling evidence showing a higher prevalence of IBS or functional dyspepsia symptoms and/or a greater symptom severity in women compared to men [ 18 22 ]. Although the underlying mechanisms linking sex hormones and gastrointestinal disturbances remain to be elucidated, intestinal dysmotility, visceral hypersensitivity, intestinal barrier dysfunction and mucosal immune activation through a brain-gut axis are thought to be involved [ 4 , 12 , 18 , 21 , 22 ]. For example, higher mucosal immune activation was found in women with IBS compared with men with IBS, and mast cell infiltration was related to greater abdominal bloating and dysmotility-like dyspepsia symptoms in women with IBS [ 23 ].…”
Section: Factors Influencing Gastrointestinal Health In Midlife Womenmentioning
confidence: 99%
“…Multivariable analyses showed that younger age, lower estrogen levels and higher anxiety were predictive of an increase in severity of abdominal pain over time, while other sex hormones and menopause transition stages were not. In a cross-sectional study among women with IBS, Lenhart et al [ 4 ] found postmenopausal women with IBS ( n = 52, a mean age of 54.4 years) experienced significantly worse severity of overall IBS symptoms, physical health-related quality of life and depression than premenopausal women with IBS ( n = 190, a mean age of 30.2 years), but no differences in abdominal pain, bloating and somatic symptoms were observed. Of note, no difference in the severity of overall IBS symptoms was found between age-matched older and younger males with IBS and thus the authors suggested the potential modulatory effects of estradiol and progesterone on brain-gut interactions.…”
Section: Factors Influencing Gastrointestinal Health In Midlife Womenmentioning
confidence: 99%
See 2 more Smart Citations
“…They are diagnosed in 35% of the adult population and in 3% of children who visit a doctor; and in 10-25% of patients with chronic diseases of the digestive system (Red`kin et al 2020). Pathogenesis and correction of constipation are of considerable scientific and practical interest, which is reflected in many modern publications (Ford et al 2018;Ballou et al 2019;Ford et al 2020;Lenhart et al 2020;Shin et al 2020) and in internationally agreed documents: Roman II, III, IV (1999,2006,2016) consensus, WGO: Practice Guideline: Constipation (OMGE2005, WCOG2017, WCOG2019). Therefore, the search for new laxatives of plant origin with a long and safe period of use is a topical issue in modern medicine.…”
Section: Introductionmentioning
confidence: 99%